Peningkatan Kemampuan Komunikasi Matematis melalui Game Based Learning Berbantuan Nearpod - Ira Aryani; Juariah Juariah; Tika Karlina Rachmawati (Universitas Ma'arif Lampung, 2025)
Mathematical communication skills are one of the skills that must be possessed when learning mathematics. One alternative to improve mathematical communication skills is by applying the Game Based Learning model assisted by Nearpod. The purpose of this study is to find out the difference in the improvement of mathematical communication skills between students who use the Game Based Learning model assisted by Nearpod and students who use conventional learning. This research used a quasi-experimental method involving two classes with a non-equivalent control group design. The instruments used was a mathematical communication skills test. The results of this research indicate that there is a difference in the improvement of mathematical communication skills between students who use the Game Based Learning model assisted by Nearpod and those who use conventional learning methods.